Advantages and Disadvantages of Inclisiran: A Small Interfering Ribonucleic Acid Molecule Targeting PCSK9-A Narrative Review - Iveta Merćep; Nikolina Friščić; Dominik Strikić; Željko Reiner (Hindawi-Wiley, 2022)
As dyslipidemias remain one of the main risk factors for developing cardiovascular disease, the question of maintaining optimal lipid levels with pharmacotherapy remains a subject of interest worldwide. In contrast to conventional pharmacotherapy, human monoclonal antibodies directed against proprotein convertase subtilisin/kexin type 9 (PSCK9) and small interfering RNA- (siRNA-) based drug targeting PCSK9 represent a new strategy for managing lipid disorders and reducing cardiovascular risk. Inclisiran is a long-acting, synthetic siRNA that targets hepatic production of PCSK9 and consequently causes a reduction in LDL-C concentrations by approximately 50% compared to placebo. The structural modification of inclisiran has led to better stability and prolonged biological activity of the drug. The main advantage over conventional pharmacotherapy and anti-PCSK9 monoclonal antibodies is its favorable administration regimen (0-90-180 days), which should lead to much better compliance. Clinical trials conducted so far have confirmed the tolerability and efficacy of inclisiran in long-term PCSK9 and LDL-C level reductions. Moreover, a short-term follow-up on the safety of inclisiran showed a relatively good safety profile of the drug. However, it is still of great importance for ongoing and forthcoming clinical trials to be continued on a larger group of patients in order to assess long-term tolerability, efficacy, and safety of inclisiran.